2020
DOI: 10.1136/ijgc-2019-000801
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the cervical microbiota of cervical cancer patients after primary radio-chemotherapy

Abstract: ObjectiveSeveral recent studies have identified a potential interaction between the vaginal microbiota and gynecological cancers, but little is known about the cervical microbiota and its changes during cancer treatment. Therefore, the aim of the study was to evaluate the quantitative and qualitative changes of cervical microbiota in patients undergoing concurrent chemotherapy and radiation treatment for locally advanced cervical cancer.MethodsCervical cytobrush samples of 15 cervical patients undergoing chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…On the other hand, Tsakmaklis et al .,[ 11 ] in 2020, evaluated by molecular methods, quantitative and qualitative changes in cervical microbiota in 8 patients undergoing chemotherapy and radiotherapy. In this study, the authors reported a considerable reduction in cervical bacterial load after chemotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Tsakmaklis et al .,[ 11 ] in 2020, evaluated by molecular methods, quantitative and qualitative changes in cervical microbiota in 8 patients undergoing chemotherapy and radiotherapy. In this study, the authors reported a considerable reduction in cervical bacterial load after chemotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in bacterial composition were analyzed at four stages of treatment, in contrast to what was reported by Tsakmaklis et al . [ 11 ] and Mubangizi et al . [ 20 ] Our results show that chemotherapy and brachytherapy decrease local bacterial diversity, in contrast to previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During CRT, a significant decrease in the bacterial load of cervical cytobrush samples was observed, while neither alpha-nor beta-diversity significantly changed [268]. Sims et al succeeded in showing that the diversity of the gut microbiota could act as pre-dictor of the survival of cervical cancer patients after CRT.…”
Section: Microbiota In Cervical Cancermentioning
confidence: 99%
“…There are no published studies yet demonstrating an impact of the FRT microbiome on response to treatment of gynecologic cancers. Changes in the vaginal and cervical microbiome were observed following pelvic radiation therapy, a commonly used primary or adjuvant treatment for cervical and endometrial cancer [95,96]. However, possible associations between the FRT microbiome and treatment response were not assessed in these small pilot studies.…”
Section: Frt Microbiome and Cancer Therapymentioning
confidence: 99%